Dual contraceptive use and associated factors among female sex workers in Gulu City, Uganda in 2023 - Bongomin, Felix; Pebolo, Pebalo Francis; Kibone, Winnie; Apio, Pamela Okwir; Nsenga, Lauryn; Okot, Jerom; Madraa, Grace; Laker, Fiona Gladys; Akello, Martha; Ouma, Simple; Musoke, David (Tropical medicine and health, 2023)
Background Dual contraception is an essential approach to mitigating the heightened risks of unintended pregnancies and sexually transmitted infections faced by female sex workers (FSWs). We determined the prevalence and factors associated with dual contraceptive use among FSWs in Northern Uganda. Methods A cross-sectional study was conducted in Gulu city, Uganda between February, and March 2023. Purposively selected FSWs aged 18 years or older who provided verbal informed consent were enrolled in the study. A sample size of 374 was estimated. Data on sociodemographic and reproductive health characteristics were collected using an interviewer-administered semi-structured questionnaire. Current dual contraception was defined the as concurrent use of a barrier and any other modern contraceptive methods within the last 3 months. Continuous variables were summarized using mean and standard deviation and categorical variables were summarized using frequencies and percentages. Modified Poisson regression analysis was used to determine factors associated with dual contraceptive use. Results We enrolled 314 FSWs, with a mean age of 28.8 ± 6.4 years. About 13.8% ( n = 41) were living with HIV. In total, 66.2% (95%CI 60.8–71.3) of the participants ( n = 208) reported current dual contraceptive use. The most common modern contraceptive method used was the implants (52.4%, n = 109), followed by injectable contraceptives (22.6.0%, n = 47), and bilateral tubal ligation (0.5%, n = 1) was the least utilized. Having had at least one previous pregnancy was positively associated with dual contraceptive use (adjusted PR: 1.87, 95%CI 1.40–2.51, p < 0.001). Conclusions A high proportion of FSWs in Gulu city were currently using dual contraceptives. Interventions are needed to facilitate the use of dual contraception, particularly among FSWs without a history of previous pregnancies.